Development of Starter Cultures for Precision Fermentation of Kombucha with Enriched Gamma-Aminobutyric Acid (GABA) Content - Geun-Hyung Kim; Kwang-Rim Baek; Ga-Eun Lee; Ji-Hyun Lee; Ji-Hyun Moon; Seung-Oh Seo (Fermentation)
Kombucha, a fermented tea beverage, is produced through the symbiotic interaction of several microbial strains, including acetic acid bacteria, lactic acid bacteria, and yeast, collectively known as symbiotic culture of bacteria and yeast (SCOBY). As its health benefits and distinctive flavor gain wider recognition, consumer demand and research on kombucha fermentation have increased. This study focused on developing starter cultures to produce functional kombucha through precision fermentation technology using selected microbial strains newly isolated from food sources. The isolated bacterial and yeast strains were evaluated and selected based on their fermentation characteristics. Notably, a lactic acid bacterial strain was chosen for its ability to overproduce the γ-amino butyric acid (GABA), a functional food component known to enhance cognitive function and reduce mental stress. To produce the GABA-fortified kombucha, selected single strains of Acetobacter pasteurianus, Lactiplantibacillus plantarum, and Saccharomyces cerevisiae were mixed and used as starter cultures. By optimizing the inoculation ratios and initial sugar concentration, a functional kombucha enriched with acetic acid, lactic acid, and GABA was successfully produced. The resulting kombucha demonstrated 2.2 mg/L of GABA production and 1.15 times higher antioxidant activity after the fermentation, highlighting its enhanced health-promoting properties.